2013
DOI: 10.4238/2013.january.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and site-directed mutagenesis of leucine-based sorting motifs of the porcine invariant chain

Abstract: ABSTRACT. Invariant chain (Ii) is a transmembrane protein that associates with MHC class II molecules in the endoplasmic reticulum. The cytoplasmic tail of Ii contains two leucine residues able to direct Ii to the endocytic pathway. We obtained the pig Ii gene by RT-PCR. Mutated Ii was prepared via site directed mutagenesis by the PCR Megaprimer method to study the effect of the two leucines on the localization of pig Ii. These mutated fragments were ligated to the vector pmCherry-C1. The recombinant plasmids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…5), indicating that the Ii chain may retain the FcRn H chain in the ER until its assembly into a complex with β2m (Ye et al, 2008a(Ye et al, , 2008b. This is consistent with studies finding that the Ii chain retains incompletely folded CD1d H chain in the ER (Jayawardena- Wolf et al, 2001), but inconsistent with studies showing that the Ii chain combines with fully folded MHC class I in the ER because Ii cannot associate with a single MHC I molecule, or the α or β2m chain (Powis, 2006;Vigna et al, 1996;Xu et al, 2013aXu et al, , 2013b. FcRn binds IgG in the slightly acidic pH of the gut lumen and releases IgG into the bloodstream of newborn animals at the neutral pH of the interstitium, pH 7.4 (Ghosh et al, 1995;Ye et al, 2008aYe et al, , 2008b.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…5), indicating that the Ii chain may retain the FcRn H chain in the ER until its assembly into a complex with β2m (Ye et al, 2008a(Ye et al, , 2008b. This is consistent with studies finding that the Ii chain retains incompletely folded CD1d H chain in the ER (Jayawardena- Wolf et al, 2001), but inconsistent with studies showing that the Ii chain combines with fully folded MHC class I in the ER because Ii cannot associate with a single MHC I molecule, or the α or β2m chain (Powis, 2006;Vigna et al, 1996;Xu et al, 2013aXu et al, , 2013b. FcRn binds IgG in the slightly acidic pH of the gut lumen and releases IgG into the bloodstream of newborn animals at the neutral pH of the interstitium, pH 7.4 (Ghosh et al, 1995;Ye et al, 2008aYe et al, , 2008b.…”
Section: Discussionsupporting
confidence: 77%
“…However, additional interactions of Ii with other molecules were found in recent studies. Xu et al indicated that Ii and the integrated MHC I molecule can form complexes that colocalize in the endomembranes of cells (Xu et al, 2013a(Xu et al, , 2013b. Ii acts as a receptor for macrophage migration inhibitory factor (MIF), alone or with CD44 (Leng et al, 2003;Naujokas et al, 1993;Shi et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ii guides antigen presentation through its N-terminal sorting signal (Landsverk et al, 2009;Xu et al, 2013). Thus, Ii has been used as immune carrier (Chen and Yu, 2010;Wälchli et al, 2014) in the construction of genetic vaccines, in which the class II-associated Ii-derived peptide domain was replaced with sequences encoding for specific antigen epitopes.…”
Section: Introductionmentioning
confidence: 99%